Statistics for national development - Sani I. Doguwa (CBN Journal of Applied Statistics, 2010)
Good statistics that has been collected according to agreed good practices are crucial as a tool for development. Gross domestic product (GDP) and other measures of economic activity such as Gross National Income (GNI) together with their individual components, show how the economy is responding to government policy and other influences. The balance of payments can demonstrate the requirement for policy adjustments and is also one of the indicators scrutinised by potential foreign investors in the country. Agricultural statistics clearly have implications for longer-term planning, particularly if they show a move away from the land into urban areas or a change in traditional farming methods. Population statistics often indicate the need for government intervention - for example, if the population is expanding so rapidly that there are major policy implications in the fields of education, housing, etc. Health-care statistics might indicate the need for a change of policy in the provision of medical services or the preponderance of particular diseases. Growth in Monetary aggregates might indicate the stance or anticipated direction of monetary policy.
Keywords: 330